S. Yu. Monakhov – J. V. Kuznetzova – N. F. Fedoseev – N. B. Churekova, Amphoras of the VI–II Centuries BC from the Collection of the East Crimean Historical and Cultural Reserve - Jefremow, Nikolai (Journal of Hellenistic Pottery and Material Culture, 2021)
The past three years have become an important event not only for Russian, but also for international ›amphorology‹. The result of many years of painstaking working on gathering, cataloguing, and finally the study of ›amphora‹ material found its way in two monographs of a group of authors under the guidance of an international-known expert in this field, professor of the university of Saratov (Russia) S. Yu. Monakhov.